2x-y 3z=-1;-4x 2y-6z=2 by gauss elimination and back substitution
1. $\displaystyle 2x-y 3z=-1$
2. $\displaystyle -4x + 2y-6z=2$
I'm guessing it's a +2y and +3z
Here, double equation 1, $\displaystyle 2x-y 3z=-1$ to get $\displaystyle 4x-2y + 6z=-2$
Or conversely you could halve equation 2.
Then you have:
1. $\displaystyle 4x -2y + 6z=-2$
2. $\displaystyle -4x + 2y -6z=2$
Wait... here I find that both equations are the exact same... You can't solve a simultaneous eauation if both of them are the same.